2004
DOI: 10.1042/bj20040253
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of muskelin identifies a conserved discoidin-like domain that contributes to protein self-association

Abstract: Muskelin is an intracellular protein with a C-terminal kelch-repeat domain that was initially characterized as having functional involvement in cell spreading on the extracellular matrix glycoprotein thrombospondin-1. As one approach to understanding the functional properties of muskelin, we have combined bioinformatic and biochemical studies. Through analysis of a new dataset of eight animal muskelins, we showed that the N-terminal region of the polypeptide corresponds to a predicted discoidin-like domain. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 57 publications
(82 reference statements)
1
45
0
Order By: Relevance
“…Muskelin associated with p48EMLP, Twa1, p44CTLH, and ARMC8α. Self-association of Muskelin, which was characterized in a previous report (Prag et al, 2004), was also confirmed in this assay (Fig. 3A, lane 3).…”
Section: Characterization Of the Associations Between Complex Componentssupporting
confidence: 78%
See 1 more Smart Citation
“…Muskelin associated with p48EMLP, Twa1, p44CTLH, and ARMC8α. Self-association of Muskelin, which was characterized in a previous report (Prag et al, 2004), was also confirmed in this assay (Fig. 3A, lane 3).…”
Section: Characterization Of the Associations Between Complex Componentssupporting
confidence: 78%
“…We identified these proteins by searches of the NCBI's non-redundant protein sequence database. The 78-kDa band was identified as Muskelin (Adams et al, 1998;Prag et al, 2004), which was previously shown to associate with RanBPM in a yeast two-hybrid system (Umeda et al, 2003). The 62-kDa band was a novel protein, ARMC8α.…”
Section: Components Of the 20s Ranbpm-containing Complex (Ctlh Complex)mentioning
confidence: 97%
“…8A). This localization was seen in all cells examined (26 of 26 cells imaged) and resembles the reported localization of muskelin in other cell types (23,24). Cells that were transfected with p39 alone showed p39 accumulation in the nucleus if expression levels were high.…”
Section: Fig 4 Mapping Of Muskelin Sites Responsible For Interactiomentioning
confidence: 56%
“…Kelch domains are structural repeats first observed in the Drosophila actin cross-linking protein Kelch that permit proteins to fold into a cylindrical, "␤-propeller structure" (22). Although several kelch domain proteins are also actin-binding proteins (22), muskelin does not bind directly to either actin or tubulin (23). It is, however, associated with the actin cytoskeleton and has multiple effects on cell adhesion and cytoskeletal structure in adherent cells (24).…”
mentioning
confidence: 99%
“…Our findings suggest that AEBP1 physically interacts with IB␣ via its DLD, which is known be a protein-protein interaction mediator (Johnson et al, 1993;Prag et al, 2004). Indeed, DLD of AEBP1 was found to be required for protein-protein interaction between AEBP1 and MAPK .…”
Section: Discussionmentioning
confidence: 76%